0077 Resiliance And Response In An Acute Trust Setting. (1st November 2014) - Dickinson, Mike; Pimblett, Mark; Lees, Lorna; Hanson, Jackie
Abstract : Background: Following a number of incidents within the trust setting in which difficult patient management dilemmas have occurred, the human patient simulation (HPS) team have formulated a "proactive" response rather than being "reactive". A number of simulated incidents that encourage the teams to take a "what if" approach to situations allowing workers to anticipate possible adverse outcomes and act in advance to avert them. 1 Method: The HPS team replicate the incidents that have occurred and staff are invited to attend in an endeavour to highlight any clinical and non technical influences on a safe patient outcome. Further more, during the debrief, the staff are encouraged to think around the dilemmas they are faced with, both clinical and non clinical to encourage them to "future" plan for any incidents they may encounter. 2 Innovation: The HPS team have developed a number of "what if" scenarios that they intend to run in clinical areas. These scenarios will be anaylsed in an attempt to highlight potential problems that could be encountered. This anticipatory method of training will be used to feedback to clinical and patient safety leads to hopefully reduce/minimise risk of incidents actually occurring. Results: Training delivered around tracheostomy emergencies is one that has been particularly well received. A further training session around cardiac arrest management in non-clinical areas e.g. stairwells has also received very encouraging feedback. Conclusions: Development of scenarios to address "what if" dilemmas, should be used to help improve patient and staff safety, and build an anticipatory response to clinical and non clinical problems. Take home message: Simulation should not only be viewed as training tool to increase skills, but it should be used as a proactive rather than reactive tool to improve patient and staff safety, and confidence. References: Minding the Gaps: Creating Resilience in Health Care.Nemeth C, Wears R, Woods D, Hollnagel E. http://www.ncbi.nlm.nih.gov/pubmed/21249930 (Online) accessed 12/6/14 National Health Service (2010) Human factor Training in the National Health Service: A Scoping Study [On Line] available from: http://www.nhsjusticegroup.co.uk/pdf/human_factors_scoping_study.pdf [Accessed 4th March 2014]